2020
DOI: 10.3897/zookeys.911.38496
|View full text |Cite
|
Sign up to set email alerts
|

Phyllodiaptomus (Phyllodiaptomus) roietensis, a new diaptomid copepod (Copepoda, Calanoida) from temporary waters in Thailand and Cambodia, with a key to the species

Abstract: Phyllodiaptomus (Phyllodiaptomus) roietensissp. nov. was collected from temporary water bodies in Roi Et and Nakhon Ratchasima provinces in northeastern Thailand and Kampong Thom Province in central Cambodia. The new species is closely related to Phyllodiaptomus (P.) surinensis Sanoamuang & Yindee, 2001 in that it shares common morphological characters in the males: urosomites 2–3, P5 intercoxal sclerite, right P5 Exp-2, and left P5 Exp. Minor differences on the right antennule, right caudal ramus, P5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…The diversity of species among the 13 genera of Diaptomidae is dominated by the genus Mongolodiaptomus, with 10 known species, followed by Tropodiaptomus and Neodiaptomus, with four species each. The numbers of species in the dominant genera in Vietnam correspond well with those reported in Thailand [8], except that Phyllodiaptomus consists of one species in Vietnam, but six species in Thailand [8,23]. However, two subterranean diaptomid species (Hadodiaptomus dumonti and Nannodiaptomus phongnhaensis) have been recorded in Vietnam [24,25], while there is no record of subterranean species in Thailand yet.…”
Section: Calanoid Copepod Diversity In Vietnamsupporting
confidence: 78%
“…The diversity of species among the 13 genera of Diaptomidae is dominated by the genus Mongolodiaptomus, with 10 known species, followed by Tropodiaptomus and Neodiaptomus, with four species each. The numbers of species in the dominant genera in Vietnam correspond well with those reported in Thailand [8], except that Phyllodiaptomus consists of one species in Vietnam, but six species in Thailand [8,23]. However, two subterranean diaptomid species (Hadodiaptomus dumonti and Nannodiaptomus phongnhaensis) have been recorded in Vietnam [24,25], while there is no record of subterranean species in Thailand yet.…”
Section: Calanoid Copepod Diversity In Vietnamsupporting
confidence: 78%
“…Phyllodiaptomus (Phyllodiaptomus) roietensis Sanoamuang and Watiroyram, 2020 (Figure 2D) was described based on specimens from Thailand and Cambodia [21]. It is a rare species, inhabiting rice fields, roadside canals, and temporary ponds only in the northeast of Thailand.…”
Section: Genus Phyllodiaptomusmentioning
confidence: 99%
“…Of the 30 calanoid species, 27 diaptomid species were reported from Southeast Asia [3]. Most of the studies were conducted in Thailand since 1994 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], while a few investigations have been documented in Cambodia [20,21,23], Laos [16,20,24], Malaysia [25][26][27], Singapore [28], the Philippines [29,30], and Indonesia [31]. A few studies were conducted in Vietnam [20], but most of the publications were published in Vietnamese with an English abstract [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A phylogenetic tree based on mitogenomes and Cytb showed that Clade 1 is restricted to the southern Guangxi Province. In addition, two P. tunguidus populations (TB and NB) near Vietnam can be considered older, if we look at the fact that most species in Phyllodiaptomus are limited to Southeast Asia ( Dumont and Reddy, 1993 , 1994 ; Dumont et al, 1996 ; Sanoamuang and Yindee, 2001 ; Sanoamuang and Teeramaethee, 2006 ; Sanoamuang and Watiroyram, 2020 ). In contrast, Clade 2 is widely distributed in many relatively isolated basins, including the Lancnagjiang River (Yunnan Dali), Upper Pearl River (Yunnan, Kunming), Lower Pearl River (Gaozhou, Guangzhou and Shaoguan), the Minjiang River (Fujian, Fuzhou) and the Yangtze River (Hunan, Changsha; Supplementary Table S2 and Supplementary Figure S1 ).…”
Section: Discussionmentioning
confidence: 99%